Estimasi Cadangan Karbon Kawasan Taman Wisata Hutan Mangrove Kecamatan Sukadana, Kabupaten Kayong Utara, Kalimantan Barat - Adityo Raynaldo; Etha Marista; Sofi Siti Shofiyah; Riza Linda; Rafdinal Rafdinal (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2022)
ABSTRACTAn assessment of the potential of mangrove forests in the Kayong Utara Regency in storing carbon has not been published scientifically before, so scientific data on this matter will be able to support efforts to conserve and utilize mangrove forests in this Regency. This study aims to estimate the carbon stock and carbon sequestration of mangrove vegetation in Mangrove Forest Tourism Park, Sukadana District, Kayong Utara Regency. The estimation of biomass, carbon stock and carbon sequestration was carried out by non-destructive methods using observation plots at several purposively selected sampling locations. The estimation results of the total vegetation biomass from Above-ground Biomass (AGB) and Below-ground Biomass (BGB) from each observation plot ranged from 281.31 – 974.10 Mg ha−1 and the total vegetation carbon stock (AGC and BGC) ranged from 126.32 – 439.03 Mg C ha−1. Analysis of the total CO2 sequestration of mangrove vegetation at the site ranged from 463.58 to 1611.24 Mg CO2 ha−1. Maintenance of mangrove forests at this site can prevent the release of non-organic carbon (CO2) with considerable potential.Keywords: Carbon sequestration, mangrove biomass, mangrove tourism, total vegetation carbonABSTRAKPenilaian mengenai potensi hutan mangrove di Kabupaten Kayong Utara dalam menyimpan karbon belum terpublikasi secara ilmiah sebelumnya, sehingga data ilmiah mengenai hal ini akan dapat mendukung upaya pelestarian dan pemanfaatan hutan mangrove di Kabupaten ini. Penelitian ini bertujuan untuk mengestimasi potensi cadangan dan serapan karbon vegetasi mangrove di Kecamatan Sukadana, Kabupaten Kayong Utara. Estimasi biomassa, cadangan dan serapan karbon dilakukan dengan metode non-destruktif menggunakan plot-plot pengamatan pada beberapa lokasi pengambilan sampel yang dipilih secara purposif. Hasil estimasi total biomassa vegetasi dari Above-ground Biomass (AGB) dan Below-ground Biomass (BGB) dari tiap plot pengamatan berkisar antara 281,31 – 974,10 Mg ha−1 dan total cadangan karbon vegetasi (AGC dan BGC) berkisar antara 126,32 – 439,03 Mg C ha−1. Analisis total serapan CO2 vegetasi mangrove di lokasi berkisar antara 463,58 – 1611,24 Mg CO2 ha−1. Pemeliharaan kawasan hutan mangrove di lokasi dapat mencegah pelepasan karbon non organik (CO2) yang memiliki potensi cukup besar.Kata kunci: Biomasa mangrove, serapan karbon, total karbon vegetasi, wisata mangrove